The Gender Safety Gap: Examining the Impact of Victimization History, Perceived Risk, and Personal Control - Logan, TK (Journal of interpersonal violence, 2021)
Previous research has documented that, in general, women are more concerned about their personal safety and take more safety precautions than men. However, this study looks beyond gender by examining the association of three overall factors including victimization history, perceived risk of future victimization, and personal control with worry about safety, safety responses, and bystander intervention intentions for 270 men and 821 women. There were four main findings from this study including the following: (a) The two most consistently associated factors with worry about safety, safety responses, and bystander intervention intentions were higher perceived risk of violent victimization and safety efficacy; (b) recent victimization, rather than victimization history, played an important role in safety responses particularly for women; (c) different patterns of factors are associated with different safety responses demonstrating the importance of examining a wide variety of safety responses; and (d) the pattern of factors associated with worry about safety and safety responses do differ by gender but also had some important similarities. Implications for future research and prevention as well as safety planning interventions are discussed.